Confucius Institute Programming in the United States: Language Ideology, Hegemony, and the Making of Chinese Culture in University Classes. - Stambach, Amy (Anthropology & Education Quarterly, 2015)
This article explores how Confucius Institute teachers and U. S. students use language to index qualities of Chinese people and culture. The study draws on the model of 'linguistic fact' to argue that students' and teachers' contextualized use of language occurs in relation to their different yet naturalized assumptions about a commonly shared social world, one they define largely in terms of market consumerism. The article offers the concept of linguistic hegemony to aid in understanding the multiple expressions of language form and use that emerge in Confucius Institute programs, and to qualify without fully discounting political scientists' claims that Confucius Institutes are ideological extensions of the Chinese state.